71.6k views
3 votes
( 3 x 2 ) ^ 4 x 3 ^ -3 / 2 ^ 3 x 3 =

Simplify the exponential expression

User ThomasFey
by
6.1k points

1 Answer

3 votes

Answer:

2

Explanation:


((3*2)^4*3^(-3))/(2^3*3)

we start simplifying by removing the parenthesis

Multiply the exponents inside the the parenthesis

3^4 * 2^4


(3^4*2^4*3^(-3))/(2^3*3)

Now we apply exponential property

a^m * a^n = a^ (m+n)

3^4 * 3^-3 = 3^ (4-3) = 3^1

3 or 3^1 are same


(3^1*2^4)/(2^3*3^1)

3^1 at the top and bottom so we cancel it out

\frac{2^4}{2^3}

we apply log property . a^m / a^n = a^m-n

Now subtract the exponents

2^(4-3) = 2^1 = 2



User Mossa
by
5.9k points